THE INFLUENCE OF LOCATION MOBILITY AND SAMAHAH SERVICE HOSPITALITY ON MOBILE COFFEE SALES VOLUME IN MEDAN CITY WITH CONSUMER BUYING INTEREST AS AN INTERVENING VARIABLE - Nanda Fitria Aulanda; Nina Annisa; Nur Fatiha Utami Nasution; Ari Prabowo (CV. Radja Publika, 2026)
This study aims to analyze the effect of location mobility and samahah service hospitality on mobile coffee sales volume in Medan City, with consumer buying interest as an intervening variable. This research uses a quantitative approach with a sample size of 400 respondents who are consumers of mobile coffee. The data analysis technique employs SmartPLS version 3 through outer model and inner model testing. The results show that location mobility has a negative and significant effect on sales volume, while samahah service hospitality has a positive and significant effect on sales volume. Location mobility and samahah service hospitality have a positive and significant effect on consumer buying interest. Consumer buying interest also has a positive and significant effect on sales volume. In addition, consumer buying interest is proven to significantly mediate the effect of location mobility and samahah service hospitality on sales volume. The findings of this study emphasize that high mobility creates a suppressor effect that reduces sales consistency, while implementing ethical hospitality and smart relocation scheduling play an important role in maximizing transaction rates.